TO EVALUATE THE MAGNITUDE OF DEPRESSION IN MULTIDRUG-RESISTANT TUBERCULOSIS PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL - SINGH, VIJAY KUMAR; KUSHWAHA, VIRENDRA; AGRAWAL, POOJA; YADAV, VEERENDRA SINGH; CHAUDHARY, DHANANJAY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to evaluate the magnitude of depression in multidrug-resistant tuberculosis patients in a tertiary care teaching hospital. Methods: An observational study was carried out in department of Psychiatry and department of Tuberculosis and Respiratory disease G.S.V.M. Medical College, Kanpur for a period of 9 months. The diagnosed multidrug-resistance tuberculosis (MDR-TB) patients coming to in-patient and out-patient department of tuberculosis and respiratory disease taking RNTCP regimen (Category IV) for MDR-TB will be screened for depression applying Hamilton Depression Rating Scale (HDRs) score and those patients who showed depression in screening will further send to psychiatry department for the final diagnosis of depression. We also categorized the patients into mild, moderate, and severe depression according to HDRs score. Data were tabulated in Microsoft Excel sheet. All categorical variables were analyzed using percentage. Results: We screened 148 MDR TB patients who were taking drug for MDRTB. The average duration of treatment were 5.19 Month. Out of 148 patients, 56 (37.84%) patients were found to be suffering from depression. Out of 56 Depressed MDR TB Patients, 35 (62.5%) were male and 21 (37.5%) were female patients and 26 (46.43%) were mild (HDRS Score-8–13), 28 (50%) were moderate (HDRS Score-14–18) and 2 (3.57%) were severely depressed (HDRS Score-19–20). Conclusion: The magnitude of depression in MDR TB Patients taking RNTCP regimen (Category IV) for MDR TB was 37.84% and out of these patients, 46.43% were mild, 50% were moderate, and 3.57% were severely depressed.